Referral and adjuvant treatment patterns after nephrectomy in high‐risk locoregional renal cell carcinoma. (9th November 2021) - Dzimitrowicz, Hannah; Esterberg, Elizabeth; Miles, LaStella; Zanotti, Giovanni; Borham, Azah; Harrison, Michael R.
Abstract: Background: It is unclear whether patients with renal cell carcinoma (RCC) are routinely assessed for recurrence risk post‐nephrectomy and whether patients at high recurrence risk are seen by providers who can evaluate candidacy for adjuvant systemic therapy (AST) and clinical trials. Materials and Methods: We identified all patients with locoregional RCC who underwent nephrectomy via an institutional database within Duke University Health System between 1 April 2015 and 31 December 2019. Medical records were reviewed to identify patient characteristics, post‐nephrectomy referrals, treatment, and follow‐up. Patients with tumor stage ≥3 and grade ≥2, regional lymph node metastasis, or both, were classified as high recurrence risk. Results: Of 618 patients with locoregional RCC who underwent nephrectomy, 136 (22%) had high recurrence risk. Of those, 25 patients with high‐risk disease (18%) were referred to medical oncology for discussion of AST; 23 (92%) of these referrals took place in 2018–2019. One patient received adjuvant sunitinib and two patients participated in adjuvant immunotherapy trials. The decision not to receive AST was primarily made by the oncologist in 10 (46%), the patient in 8 (36%), and unrecorded in 4 (18%) of 22 cases, for multiple reasons. Individual surgeons referred high‐risk patients for discussion of AST with varying frequency, ranging from 0% to 100% in 2019. Conclusions: Despite increasing number of patients with locoregional RCC at high recurrence risk referred to medical oncologists after nephrectomy, few patients received AST, including participation in clinical trials. With increasing AST options and ongoing clinical trials in this space, these findings highlight the need for continued efforts at identifying effective AST and referring patients most likely to benefit to medical oncologists. ClinicalTrials.gov, NCT04309617. Abstract : We identified all patients with locoregional renal cell carcinoma who underwent nephrectomy between 1 April 2015 and 31 December 2019 to characterize patient characteristics, patients at high recurrence risk, post‐nephrectomy referrals, treatment, and follow‐up. Despite increasing number of patients with locoregional RCC at high recurrence risk referred to medical oncologists after nephrectomy (23 of 25 referrals taking place in 2018‐2019), few patients (n=3) received adjuvant systemic therapy, including participation in clinical trials.